Hygrothermal Performance of Cool Roofs Subjected to Saudi Climates - Saber, Hamed H.; Maref, Wahid; Hajiah, Ali E. (Frontiers in Energy Research, 2019)
When solar radiation hits a roof surface, a part of solar energy is reflected and another part is absorbed. The absorbed part of solar energy results in an increase of the surface temperature of the roof. Cool (white) roofs use bright surfaces to reflect a significant portion of the incident short-wave solar radiation, which lowers the surface temperature compared to conventional (black) roofs. As such, white roofs help reduce the urban heat island effect during the summer. The questions are: (a) do white roofs lead to moisture-related problems in Saudi climates? (b) what are the amount of energy savings as result of using white roofs instead of black roofs of same insulation amount, and (c) what is the reduction in the amount of insulation in the white roof having the same energy performance level as the black roof? To answer these questions, numerical simulations were conducted for one type of roof that is commonly used in low-rise buildings of Saudi Arabia in order to assess and compare the energy and hygrothermal performance of white and black roofs. The roof was subjected to weather conditions of the Eastern Province of Saudi Arabia. The indoor conditions were taken based ASHRAE recommendations for conditioned space. The main outcome of this study has shown the capabilities of using reflective materials with different short-wave solar absorption coefficients for enhancing the energy performance of roofs and/or reducing the amount of insulation that resulted in same energy performance as black roofs. This study can be used in future for upgrading Saudi Building Code to allow less roof insulation if reflective roof is installed.